FORMULASI SEDIAAN LULUR PENCERAH DAN PENGHALUS KULIT DARI KUNYIT (CURCUMA LONGA LINN) - Rani Prabandari (Universitas Harapan Bangsa Purwokerto, 2018)
ABSTRACT Lulur is a type of cosmetics made from flowers and other plant ingredients that are very useful for maintaining beauty, health, smoothness and brightness of the skin of the body. Scrub can help clean the dirt that sticks to the skin due to the influence of weather factors and pollution so that the skin becomes healthy, clean and beautiful. Dry skin types often tend to be more problematic than other skin types. Dry skin is caused by insufficient oil produced by the kelenjer oil, which makes the skin not moist and dry. This can cause skin problems such as: skin looks rough, wrinkled and dull. The contents of the substance include turmeric: curcuminoid which consists of curcumin, desmetoksikumin and bisdesmetoksikurkumin and other beneficial substances, such as volatile essential oils of oil, fat, carbohydrates, protein, starch, vitamin C, iron, phosphorus, and calcium. Curcumin is a yellow substance contained by turmeric, on average 10.29%, has broad spectrum biological activity including antihepototoxic, antibacterial and antioxidant so that turmeric is able to be used for traditional medicine both maintaining health and beauty of the body's skin, the method used to carry out this research is an experiment. The object in this study is the skin of the body found on dry skin in the hands. The sample in this study the author took the students of the University of Harapan Bangsa Purwokerto Pharmacy Department especially women aged 19-25 years, have the same characteristics / criteria that indicated dull, rough and not bright skin. Keywords: formulation, scrub, turmeric, lightening.